Fibroblast Growth Factor‐23 and Heart Failure With Reduced Versus Preserved Ejection Fraction: MESA - Mohamed Faher Almahmoud; Elsayed Z. Soliman; Alain G. Bertoni; Bryan Kestenbaum; Ronit Katz; João A. C. Lima; Pamela Ouyang; P. Elliott Miller; Erin D. Michos; David M. Herrington (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Higher fibroblast growth factor‐23 (FGF‐23) levels are associated with incident heart failure (HF) in MESA (the Multiethnic Study of Atherosclerosis). FGF‐23 is also associated with left ventricular hypertrophy. Whether the FGF‐23 association with HF is similar for heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF) is not well established. Methods and Results We studied 6542 participants (mean age 62±10 years, 53% women, mean estimated glomerular filtration rate of 81±18 mL/min per 73 m2) from MESA who were free of cardiovascular disease at baseline (2000–2002). HF events were ascertained by an adjudication committee for a median follow‐up of 12.1 years. We classified HF events as HFrEF (ejection fraction [EF] <50%) or HFpEF [EF] ≥50%) at the time of diagnosis. Cox proportional hazard regression was used to compute hazard ratios and 95% confidence intervals for the association between baseline serum FGF‐23 and incident HFrEF and HFpEF. A total of 134 events were classified as HFpEF, 151 HFrEF, and 49 unknown EF. Following imputation, 149 were classified as HFpEF, 176 HFrEF, and 291 participants had HF (34 participants had HFpEF then HFrEF). In the fully adjusted model, higher FGF‐23 levels were associated with incident HFpEF but not with HFrEF (hazard ratio 1.29, 95% confidence interval, 1.08–1.54) versus (hazard ratio 1.04, 95% confidence interval, 0.84–1.29) for each 20 pg/mL higher serum FGF‐23 concentration. Conclusions FGF‐23 association with HF is driven by the association with HFpEF but not with HFrEF in a population‐based cohort. Further studies are needed to determine the pathological mechanisms mediating this association.